Human alpha defensin CNV haplotype diversity - Xu, Xiao (2018)
Humans have highly variable number of alpha defensin genes, with between 3-16 diploid copies. Alpha-defensin genes have important roles in human innate immunity and diseases. Recently, GWAS studies reported this locus associated with IgA nephropathy and periodontitis. However, the underlying mechanism of association is not clear. In this Ph.D. thesis, human alpha defensin CNV flanking haplotype diversity in global populations was studied and the association between diseases and haplotype classes was discussed. Then a novo method to detect variants from inside the DEFA1A3 CNV was developed and a list of potential disease-related mutations for further functional studies was generated. The association between CNV internal variants and flanking haplotype classes was studied. Non-allelic homologous recombination was found to be the major mechanism of CNV formation of alpha defensin CNV. Analysis results were verified by PCR and Sanger sequencing-based methods. Additional to that, the haplotype diversity analysis highlighted an unusual haplotype 5T/7C which is only found in European populations but highly diverged from other human haplotypes. Further evidence was provided to suggest that this is an introgressed haplotype from Neanderthals. Furthermore, we used Oxford Nanopore to reconstruct haplotype structure in DEFA1A3 CNV and discussed its advantages and limitations by our analysis results. In brief, this Ph.D. research greatly improved our understanding of DEFA1A3 global diversity, evolutionary history, diseases and haplotype association.